Temas de introducción al derecho. Carlos Gaviria Díaz. Señal Editora,Medellín, 1992. - Hoyos Hurtado, Clemencia (Estudios de Derecho, 1991)
Temas de introducción al derecho. Carlos Gaviria Díaz. Señal Editora,Medellín, 1992.